MAKLUMAT INDUSTRI DAN SAINS INFORMATION SERVICE FOR COMMERCE & INDUSTRY - Perpustakaan, Hamzah Sendut (Perpustakaan Universiti Sains Malaysia, 2003)
PROTEOMICS MAY CHOOSE MALAYSIA AS REGIONAL BASE Proteomics International, a Western Australian biotechnology company, may choose Malaysia as a regional base to expand into the South-East Asian market, sources were quoted. Proteomics involves the study of the interaction of genes, proteins and disease. Proteomics has the potential to create significant alterations in pharmaceuticals. Existing research and development initiatives conducted by Proteomics International include agricultural, microbial and medical projects.